2016
DOI: 10.18697/ajfand.73.15875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bap, Naa and Ga3, Either Alone or in Combination, on Meristem Culture and Plantlet Establishment in Sweet Potato (Cv Brondal)

Abstract: In Zimbabwe, the average sweet potato yield (6 t/ha) is relatively low when compared to Asian counterparts (17 t/ha). These low crop yields have been blamed on weevil infestations and viral infections which account for 60-90% of sweet potato yield losses in Africa. Meristem tip culture, a Centre for Potato Improvement (CIP) initiated tissue culture technique, has been widely used to eradicate viruses from clonally propagated crops and has been noted to be one of the instrumental techniques that helped China to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…A previous study (El Far, 2007) found that neither IAA, NAA, nor GA3 enhanced shoot proliferation in 'Abees' sweet potato but that GA3 enhanced shoot elongation. However, the combination of high concentration GA3 (10 mg L -1 ) and 2 mg L -1 BA improved adventitious shoot regeneration in 'Brondal' sweet potato to a mean of three shoots per meristem, with three nodes per shoot (Masekesa et al, 2016). Although silver nitrate has been used widely as an additive for in vitro propagation (Kumar et al, 2009), it failed to improve shoot multiplication in 'Abees' sweet potato, and although the combination of 2 mg L -1 BA and 100 mg L -1 oxalic acid significantly increased shoot number, maximum shoot length was observed on the medium that was supplemented with oxalic acid (200 mg L -1 ) alone.…”
Section: Effects Of Other Additives On Axillary Shoot Multiplicationmentioning
confidence: 96%
“…A previous study (El Far, 2007) found that neither IAA, NAA, nor GA3 enhanced shoot proliferation in 'Abees' sweet potato but that GA3 enhanced shoot elongation. However, the combination of high concentration GA3 (10 mg L -1 ) and 2 mg L -1 BA improved adventitious shoot regeneration in 'Brondal' sweet potato to a mean of three shoots per meristem, with three nodes per shoot (Masekesa et al, 2016). Although silver nitrate has been used widely as an additive for in vitro propagation (Kumar et al, 2009), it failed to improve shoot multiplication in 'Abees' sweet potato, and although the combination of 2 mg L -1 BA and 100 mg L -1 oxalic acid significantly increased shoot number, maximum shoot length was observed on the medium that was supplemented with oxalic acid (200 mg L -1 ) alone.…”
Section: Effects Of Other Additives On Axillary Shoot Multiplicationmentioning
confidence: 96%
“…cultivar, while addition of 1 mg/L BA alone to medium induced the shoot regeneration at about a 1% rate. The presence of BA either alone or combined with NAA or GA 3 was proven to be necessary for shoot initiation [ 64 ]. BA level was crucial to increase the shoot initiation percentage of other cultivars of sweet potato ( I. batatas (L.) Lam.…”
Section: Meristem Excision and Culturementioning
confidence: 99%
“…cultivar; regardless, there were no significant differences between shoot regeneration capability of meristems cultured on media with 5.0, 10.0, and 20.0 mg/L GA 3 content. However, the most shoots were obtained on the medium containing 10.0 mg/L GA 3 due to multiplied shoots developed on meristems [ 64 ].…”
Section: Meristem Excision and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…MS medium supplemented with 1 mg/L 6-BA, 0.1 mg/L IBA, and 2 mg/L GA 3 promoted shoot elongation significantly in Cerasus campanulata (Wang and Huang, 2002 ). In sweet potato, the combination of 10 mg/L GA 3 and 1 mg/L 6-BA could give rise to significantly taller shoots (20 mm) compared to the rest of the treatments (Masekesa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%